Relational Selling, Relationship Quality, and Future Behavioural Intentions in the Health Insurance Industry - Rai, Shivaprasad; Basri, Savitha (Indian Journal of Marketing, 2019)
The convoluted nature of health insurance necessitates sharing of complete, accurate, and timely information to assist the customers to make suitable product choices. The insurance agents should capitalize their technical expertise by carrying out need analysis and engage in relational selling behaviour (RSB) to enhance relationship quality (RQ), namely Trust and Satisfaction. The Future Behavioural Intentions (FI) of customers manifested in repurchase intentions and willingness to recommend rely on Trust and Satisfaction with agents' services. After identifying the literature gap in explicating the effect of RSB on RQ and ultimately on FI, this study was carried out in Karnataka using descriptive cross-sectional survey methodology. The data from customers were collected using established scales, and the data were analyzed by applying partial least square structural equation modelling. The results indicated that customer orientation directly influenced Trust and FI; whereas, information sharing enhanced Trust and Satisfaction, and thereby affected FI. Therefore, insurance companies should stress on customer-orientation and disclosure of relevant information and focus on building a high-quality agent-buyer relationship that would ensure renewal of policies and positive word of mouth.